ASSESSMENT OF COMPENDIUM OF THE TURKIC DIALECTS (=Diwan lugat at-Turk) IN TERMS OF ARABIC LEXICOGRAPHY - Faruk ÖZTÜRK (Fırat University, 2019)
In Arab language such words as mucam, kamus, lugat correspond to the word dictionary. The beginning of the lexicography in Arab language corresponds to the time, when Prophet Muhammed gave explanations to the unknown words from the Koran and legends, and those who was listening Prophet’s sermons, having learned these words by heart wrote them down and retold. The first work devoted to this theme was written by ??? ???? Ibn Abbas named “???? ?????? garibu ’l-kuran”. The work “Compendium of The Turkic Dialects (=Diwan lugat at-Turk)” in this work was compared with the full Arab dictionary “kitabu ’l-ayn’”. Their similarities and differences were established. “Diwan lugat at-Turk” was also compared with the dictionary “Divanu ’l-adab”. Mahmud Kashgarskiy was under the influence of this work when he was writing his own. Arab vocabulary entries from “Diwan lugat at-Turk” and “kitabu ’l-ayn” are fixed in the table at the end of work.